Osmium- and ruthenium-antimony carbonyl clusters and rings - Li, Yingzhou (2016)
The reaction of the lightly stabilized cluster Os3(CO)11(NCCH3) with the hydrostibine SbPh2H afforded the four-membered ring Os3(H)(CO)11(μ-SbPh2). A similar reaction with the distibine Sb2Ph4 gave the analogue Os3(SbPh2)(CO)11(μ-SbPh2), which can be regarded as a metalloligand with the presence of a lone pair on the terminal SbPh2 group. Reactions of the Sb2Ph4 with the M3(CO)10(NCCH3)2 (M = Ru or Os) afforded the clusters M3(CO)10(μ-SbPh2)2, which featured fluxional M–M bonds. These clusters undergo ligand substitution reactions with two electron donors L to form M3(CO)9(L)(μ-SbPh2)2 or M3(CO)8(L)2(μ-SbPh2)2, and oxidative addition reactions with halogens X2 (X = Cl, I) to afford five-membered rings, or with the halo- and hydrostibines SbPh2X (X =Cl, H) to afford the fused ring products M3(X)(CO)9(μ-SbPh2)3. Reaction of the halostibine SbPh2Cl with Os3(CO)11(NCCH3) or Os3(CO)10(NCCH3)2 afforded the four- or five-membered metalloheterocycles Os3(Cl)(CO)11(μ-SbPh2) or Os3(Cl)2(CO)10(μ-SbPh2)2, respectively. A raft-like, higher nuclearity cluster Os6(CO)20(μ-SbPh2)2 was also isolated from the first reaction. With SbPhCl2, the reaction of Os3(CO)11(NCCH3) afforded two isomers of Os3(Cl)2(CO)11(μ3-SbPh). The latter could lose an Os(CO)3(Cl)2 fragment with PMe3 to form a “closed stibinidene” Os2(CO)8(μ3-SbPh), which could be trapped with W(CO)5(thf). These reactions led to complex mixtures with the corresponding ruthenium precursors. A better approach was through either the carbonylate [HRu3(CO)11]-, which afforded Ru–Sb clusters under mild conditions, or ketyl radical initiation of Ru3(CO)12 which afforded a higher nuclearity cluster Ru6(CO)20(μ-SbPh2)2 in a moderate yield.